2018
DOI: 10.2166/wst.2018.078
|View full text |Cite
|
Sign up to set email alerts
|

Activity assessment of microalgal-bacterial consortia based on respirometric tests

Abstract: Respirometric techniques are useful tools to evaluate bacterial activities in activated sludge processes due to their fast execution and the possibility to obtain several kinetic parameters from a single test. Using such techniques in microalgae-bacteria consortia treating wastewater could allow a better understanding of mutual interactions between the microbial populations as a function of environmental parameters. This work aims at developing and testing a novel experimental respirometric protocol to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…Microscopic observation revealed that the inoculum was made of a mixed microalgae/bacteria community including mainly Scenedesmus spp. and Chlorella spp., in agreement with previous studies [24][25][26][27].…”
Section: Pilot Plant and Experimental Designsupporting
confidence: 94%
“…Microscopic observation revealed that the inoculum was made of a mixed microalgae/bacteria community including mainly Scenedesmus spp. and Chlorella spp., in agreement with previous studies [24][25][26][27].…”
Section: Pilot Plant and Experimental Designsupporting
confidence: 94%
“…For this procedure, 0.8 mL of ammonium chloride (3 g/L) was added as the ammonium source. Among the different ammonium sources that have been used to evaluate nitrifying activity in activated sludge processes and microalgae-bacteria consortia, ammonium chloride has been the most extensively utilized [17,18]. The sample was exposed to four light-dark cycles of 4 min each.…”
Section: Photosynthesis and Respiration Rate Measurementsmentioning
confidence: 99%
“…However, respirometry methods have been generally applied to pure microalgae cultures, while in wastewater processes is indispensable to consider the existence of microalgae-bacteria consortia. On this issue, some authors have started to develop respirometry methods for studying microalgae-bacteria consortia by evaluating both microalgae and bacterial activity, specifically nitrifying activity in microalgae wastewater treatment [17].…”
Section: Introductionmentioning
confidence: 99%
“…A first approach on the evaluation of nitrite inhibition (at lab-scale) was carried out by respirometries, which allowed obtaining the OPR of microalgae. OPR was selected as an indicator of microalgae performance as it has been widely reported to be proportional to microalgae photosynthetic activity (Rossi et al, 2018).…”
Section: Short-term Exposure To Nitritementioning
confidence: 99%
“…It must be noted that the OPR obtained by Eq. 1 corresponds to a net value which is the result of several processes: i) microalgae photosynthesis; ii) activity of nitrifying bacteria; iii) respiration of heterotrophic bacteria; and iv) microalgae photorespiration (Rossi et al, 2018).…”
Section: Short-term Exposure To Nitritementioning
confidence: 99%